Insuring non-verifiable losses - Neil A. Doherty; Christian Laux; Alexander Muermann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
Insurance contracts are often complex and difficult to verify outside the insurance relation. We show that standard one-period insurance policies with an upper limit and a deductible are the optimal incentive-compatible contracts in a competitive market with repeated interaction. Optimal group insurance policies involve a joint upper limit but individual deductibles and insurance brokers can play a role implementing such contracts for the group of clients. Our model provides new insights and predictions about the determinants of insurance.
urn:nbn:de:hebis:30:3-241157
Keywords: D6; G22; L14; 330; Deductible Insurance; Upper Limit; Implicit Insurance Contracts; Insurance Brokers; Versicherungsökonomik; Anreizvertrag; Selbstbeteiligung; Versicherungsvermittlung; Theorie